The question of participation: toward authentic public participation in public administration - King, Cheryl Simrell; Susel Bridget, O'Neill; Feltey, Kathryn M. (1998)
How can the process of public participation be improved? This study uses interviews and focus-group discussions to look for some answers. The results suggest that improving public participation requires changes in citizen and administrator roles and relationships and in administrative processes. Specifically, we need to move away from static and reactive processes toward more dynamic and deliberative processes. The article suggests some practical steps to achieve these changes. - Reproduced
Keywords: Public administration